Assessment Of Standard Landfill Criteria For Planning New Landfill Sites - Saeed, Mohamed Osman (2012)
Selection of sanitary landfill site based on environmental, engineering, economic and socio-political criteria are the key determinants in urban planning and development. The primary goal of this study is to evaluate the engineering and environmental aspects of landfill site using direct feedback from decision makers (DMs) of landfill management communities in Malaysia. These results were further validated by carrying out landfill site selection using geographic information system (GIS) on a study area at Seberang Perai, Pulau Pinang. The entire process is accomplished firstly by using input data (decision criteria) collected and evaluated using the statistical and mathematical models. A suitable weighted decision model was proposed for quantifying landfill criteria based on DMs’ preferences which play a significant role in designing suitable sanitary landfill for Pulau Pinang. This was further supported by GIS software for multiple criteria suitability model which utilizes AHP in determining feasible sites for new sanitary landfill in Seberang Perai Selatan (SPS). An AHP survey was designed and carried out among selected DMs of government organizations (GOs), mainly from municipalities of selected cities and towns as well as non-government organizations (NGOs). These selected experts are basically from municipalities, universities, private companies and research centers.